Urban systems dynamics and emergent morphologies under the neoliberal socio-economic restructuring: Moscow and Shenzhen as case studies - Smirnova, Vera (Kansas State University, 2014)
In recent years urban planners have seen critical changes in the scales, pace, and trends of urbanization, resulting in suppressed urban patterns and the emergence of distinctive types of urban dynamics. A possible interpretation of this process is that it represents a “radical socio-spatial restructuring under the regime of global neoliberalization”, a phenomenon that is being widely discussed by many influential planners, urban geographers, and sociologists. My overarching research agenda is to develop a new analytical framework for comparative quantitative analyses of neoliberal urbanization pressures that cause the emergence of distinct patters of urban dynamics and morphologies. By comparing different experiences of ongoing urban transformations around the world and studying the mechanisms of their emergence, we can identify contemporary trends, monitor critical changes and shape a better future for our cities. Using China as a basis of comparison, my thesis seeks to challenge the unproductive and homogeneous patterns of urban dynamics that emerged during neoliberalization in Russia. The controversial and extremely heterogeneous model of Chinese urbanization cannot be applied universally, but valuable lessons can be derived. My work aims to explore specifics of two different patterns of neoliberal transitions in Moscow (Russia) and Shenzhen (China) in 1992 and 1978 respectively. By focusing on detailed scales of restructuring of urban settlement typologies I identify the characteristics of socio-spatial patterns prior to confronting the transition and its resulting outcomes. While considering potential context specific properties of East Asian urbanization, I am making an attempt to extrapolate this vernacular experience into generalized theory. Connecting and quantifying local and global dimensions of urban transformations helps me build a comprehensive theoretical and quantitative framework for a more profound understanding of ongoing socio-spatial restructuring.
Keywords: Urban theory; Urbanization; Neoliberal transition; Urban dynamics; Moscow; Shenzhen; Architecture (0729); Area Planning and Development (0341); Urban Planning (0999)